PREVENTION OF INFECTIOUS ASPECTS OF DOUBLE BRAIN INJURIES - Kuldasheva , Yairakhan; Khaidarova , Feruza; Kakhramonjon , Kakhramonjon; Khodjaliev , Takhirjon; Khodjaliev , Jakhongir; Kholmatov , Azizjon; Akbarov , Ikram; Inomova, Gulmira (Medical science of Uzbekistan, 2023)
Traumatic brain injury (BMJ) is considered an important medical and social problem, and it is of great importance due to its wide distribution, high rate, and disability among the active age population. Purpose: to study the specifics of the development of infectious-inflammatory complications in the prevention and treatment of TBI (double head injuries). Material and methods During 2015-2022, the cases of 615 patients hospitalized in the departments of traumatology, neurosurgery and neuroreanimation at the Andijan branch of the Republican Urgent Tibial Erdam Scientific Center were studied. Traffic accidents were identified in 394 (64%), domestic 160 (26%), falls from height 37 (6%), production-related 18 (2%), sports-related 6 (2%) cases. BMJ and musculoskeletal injuries occurred in 283 (46%), spinal cord and spine injuries in 178 (29%), thoracic cage injuries in 123 (23%) and iliac bones injuries in 31(2%). 80 (13%) patients were injured under the influence of alcohol. Purulent-inflammatory complications of the brain were studied in BMJ through analyzes of patients who developed meningitis and meningoencephalitis in the acute period. Along with other analyzes conducted in the BMJ, the results of CSF implantation in patients were also examined. Results Out of 270 patients diagnosed with severe CBMJ, purulent-inflammatory complications (meningitis and meningoencephalitis) were more characteristic of focal injuries than diffuse injuries (18%). This situation may depend on the mechanism of CBMJ acquisition (diffuse injuries - rotational-angular mechanism acceleration-deceleration, focal injuries - against blow-by-blow). Analyzes of severe SCI in the presence of infectious complications of the brain show that the number of deaths was statistically higher when these complications developed. In general, the incidence of disability and good recovery among the remaining patients is correspondingly reduced.